DWRB137: Six row, high yielding and stripe rust resistant feed barley for irrigated timely sown conditions of north eastern plains zone and central zone - Goyal, Vishnu Kumar; Kumar, Dinesh; Kharub, Ajit Singh; Singh, Gyanendra Pratap (Journal of Cereal Research, 2018)
Barley variety DWRB137 was released by the CVRC and notified vide Gazette notification S.O. 1379 (E) dated March 27, 2018, for irrigated timely sown conditions of northeastern plains zone and central zone. During the coordinated evaluation, the variety DWRB137 showed mean grain yield of 42.49q/ha with genetic potential of 67.44q/ha in the centralÂ zone. DWRB137 exhibited grain yield superiority of 10.67 (BH959), 9.01 (PL751) and 5.46 (RD2786) percents over the central zone check varieties. In northeastern plains zone, the genotype DWRB137 depicted a mean grain yield of 37.93q/ha and showed grain yield superiority over the checks namely Jyoti (10.20%), K508 (10.05%) and HUB113(5.00%), respectively. The six-row barley variety DWRB137 showed the highest reaction of 5MS for yellow rust with ACI of 1.00 under artificial inoculations in coordinated disease screening nurseries. In six row segment, the variety DWRB137 depicted overall good malting quality with 90 percent bold grains, hectolitre wt. of 61kg/hl, grainÂ beta-glucan of 4.9%, malt yield of 87.1%, and diastatic power of 1020L, respectively. DWRB137 has erect growth habit, erect flag leaf and compact plant type with dense and pale green spikes.